Sosialisasi Tentang Senam Kaki Pada Penderita Diabetes Melitus Tipe II Di Wilayah Kecamatan Tabunganen - Ariani, Sri Purwanti; Jamilah, Sri; Indria, Rekha (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Diabetic foot exercises can be given to all DM patients with Type I or Type II and it is best to provide this therapy since the patient is diagnosed with Diabetes Mellitus as a measure to prevent complications as early as possible due to Diabetes Mellitus. Foot exercises can help improve blood circulation, strengthen the small muscles of the feet, and prevent foot deformities in people with Type II Diabetes Mellitus. Blood flow to the feet will help stimulate the nerves of the feet in receiving stimulation, this will increase the sensitivity of the feet in receiving stimulation. Apart from that, if you don't do leg exercises it can result in narrowed or blocked blood vessels, this can cause ineffective peripheral perfusion. To overcome this problem, it is necessary to provide foot exercises to people with Type II Diabetes Mellitus, because doing foot exercises can prevent ineffective peripheral perfusion. The method used was socialization about foot exercises for diabetes mellitus sufferers with the result that the community was enthusiastic about the implementation of foot exercises in the outer terrace village area of ​​Tabunganen sub-district. The conclusion was that the majority of people were able to carry out foot exercises independently.